Incidencia de la comunicación intercultural en la divulgación de costumbres y tradiciones autónomas de la Comunidad del Puerto Bajaña cantón Buena Fe año 2022 - Tobar Palma, Victor Eduardo (2022)
The method used in this research is of two qualitative and quantitative approaches, important to detail the problem in a precise way with the possible existing and suggested solutions; field research has been used to adequately obtain information from the residents of the Bajaña port. The inductive and deductive methods used in this research allowed us to determine the incidence of intercultural communication in the transmission and dissemination of the way of life (culture) of the citizens of Puerto Bajaña; The primary technique such as the survey, adding the questionnaire as a tool or instrument to collect more specific data on the population of the Bajaña port, allowed us to demonstrate how intercultural communication benefits community development. The sector where the investigative work was carried out has a population of 200 citizens, of which a sample of 150 citizens of the community was selected, the method used for the selection of the sample was computational methods, in which it was concluded that In a favorable way, the acceptance of the proposals and recommendations was also determined that with the dissemination of intercultural communication, the customs and traditions of the community of the port of Bajaña, Cantón, can be rescued.